Theoretical and applied significance of systematics, its methodologies in the study of aphids (Homoptera, Aphidoidea) - Mamontova, V.A. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
The literature data and the author’s own research, have exhaustively proved that taxonomy provides a framework for all other studies in entomology.The main thing in the taxonomy is full compliance with the genealogical tree of the study group, i.e., its evolutionary path determining the phylogeny of the group.There are two accepted methods for compiling the system and species determination: “evolutionary taxonomy”, which the author of the article is based on and economical computer Hennig’s “phylogenetic systematics” (Hennig, 1954, 1956) or cladistics. Specific examples show that the preference to cladistics among foreign aphidologists leads to by no means reliable conclusions, inconsistent with the systems under study. Even carried out at the high molecular level (Normark, 2000), it does not save the family tree from errors and conventions.Thus, cladistic methodology in the study of aphids (due to their complex biology, and polymorphism in particular) is completely unacceptable. Only evolutionary taxonomy, based on A. N. Severtsov’s and his school teaching «Morphological Patterns of Evolution» is allowable.